Positional Power, Strikes and Wages - Perrone, Luca; Wright, Erik Olin; Griffin, Larry J. (American Sociological Review, 1984)
Some time ago, Eric Olin Wright asked whether the ASR would entertain the possibility of publishing a paper written by the late Luca Perrone and edited by Wright, with the understanding that the paper contained serious flaws that under the circumstances could not be corrected through the review process. I said that we would, that I would inform reviewers of the circumstances and ask them to evaluate the paper, not against the standard of what it might become were their comments considered and acted upon, but rather against the standard of its value as it stood. The comments of the referees and my own reading of the manuscript made it clear that the paper contained flaws, but that it also contained potentially important and useful ideas. I decided that on balance the paper, in reduced form, warranted publication. I also decided, as a substitute for the changes in the manuscript that might have followed had Perrone been able to respond to the critiques of his paper, that it would be useful to publish along with the paper the postscript Wright had prepared and a synopsis of referees' comments. Larry J. Griffm shortened the paper, and also prepared the